Collapsed Concerto Grosso Analysis of Alfred Schnittke’s Concerto Grosso no. 1 from a violinist’s point of view - Rajic,Anja (2025)
This study explores the interpretative and technical demands placed on the violinist in Alfred Schnittke’s Concerto Grosso No. 1, with particular attention to the work’s dialogue between past and present. Through a detailed examination of its violin parts, the research investigates advanced bowing, articulation, and intonation strategies required for performance, as well as efficient practice methods. Formal analysis highlights Schnittke’s reimagining of the Baroque concerto grosso structure—concertino and ripieno relationships, episodic writing, and contrapuntal textures—juxtaposed with twentieth-century idioms and extended techniques. By comparing these features to the traditional Baroque concerto grosso model, the paper reveals how Schnittke both subverts and revitalizes historical forms, offering performers insight into historically informed yet modernist approaches to the piece.
Keywords: Score analysis; practice; polystylism; baroque style; late 20th century music